Theology and religious studies in higher education global perspectives - Bird, Darlene; Smith, Simon G. (London ; New York : Continuum, 2009)
Theology and religious studies co-exist in the majority of departments in higher education institutions within the UK, yet there has been very little debate or discussion on how these two disciplines relate to one another in this context and on a more general level. This new collection of essays aims to redress the balance and to add to fruitful discussion in this area Including essays by some of today's leading academics on the sometimes contentious relationship between religious studies - or the study of religions - and theology, this volume is international in scope, with contributions from
Religious studies versus theology : why I'm still glad that I converted from theology to religious studies / Denise Cush -- Theology and religious studies for a multifaith and secular society / David F. Ford -- Theology and religious studies, or theology versus religious studies? / Gavin D'Costa -- Theology as the past and future of religious studies : an incarnational approach / Erik Borgman and Stephan van Erp -- The irony of religious studies : a pro-theological argument from the Swedish experience / Mattias Martinson -- The inevitability of normativity in the study of religion : theology in religious studies / Thomas A. Lewis -- Towards a socio-cultural, non-theological definition of religion / James L. Cox -- A spatial analysis of the relationship between theology and religious studies : knowledge-power strategies and metaphors of containment and separation / Kim Knott -- "A coat of many colours" : interweaving strands in theology and religious studies / Ursula King -- Interdisciplinary theology : bridging the theology/religious studies divide / Shannon Craigo-Snell -- Recent developments in theology and religious studies : the South African experience / J. Jarvis and C.A.E. Moodie -- The place of theology in Iranian universities : the challenges of teaching theology in modern Iran / Mohammad Sadegh Zahedi -- The Bible : fringe or hinge? / Hugh Pyper.
Includes bibliographical references and index.
Keywords: Religion -- Study and teaching -- Congresses; Theology -- Study and teaching -- Congresses; Universities and colleges -- Curricula -- Congresses; Religion; RELIGION -- Christian Theology -- General; Electronic books